Typifications and a new synonym in Phyllanthus sect. Phyllanthus subsect. Clausseniani (Phyllanthaceae) - Mendes, Jone Clebson Ribeiro; Silva, Marcos José Da; Pereira-Silva, Rafaela Alves; Sales, Margareth Ferreira De; Athiê-Souza, Sarah Maria (Phytotaxa, 2021)
Six names in Phyllanthus sect. Phyllanthus subsect. Clausseniani are typified (P. amoenus, P. claussenii, P. claussenii var. oblongifolius, P. heteradenius, P. hypoleucus, and P. janeirenis). Phyllanthus atalaiensis is treated as a synonym of P. heteradenius.